PATTERN OF PLATOON DISPERSION DUE TO DRIVER BEHAVIOR AT SIGNALIZED INTERSECTIONS (Wudil Journal of Science and Technology Education, 2025)
With evidence of decrease in efficient flow portraying induced discharge flow pattern atsignalized intersections mainly due to the drivers behaviours, the research provides empiricalevaluation into the most conspicuous behaviours especially phone distractions and trafficviolations along the subject approaches of three distinct signalized intersections within KanoMetropolis along three dual three-lane motorways. The research employed field observationalmethod to assess the impacts of drivers’ behavior of cell-phone usages and traffic violationsthrough green duration. It was observed after analysis; the highest distractive behaviour bydrivers is use of cell-phone gulping SLT of 0.3-0.5 seconds against 0.1- 0.8 seconds of otheractivities or more respectively, constituting more than half capacity loss of the traffic. Theheadway of the traffic is impacted by an increase in 1 seconds for a single cell-phone user whichposed a stabilizing effect with varying increase of 0.3 seconds when other any mix of activitiesare added. This concludes a variety of driver behavior having impact in different manner on theintegrity of the traffic. The models provided may help researchers, practitioners, and policymakers among other stakeholders in formulating and employing various interventions andstrategies to a more cordially, safe, effective and efficient traffic operations within and beyondsignalized intersections. Better signal timing and social intervention is recommended to beappropriated. Whilst the data collection methodology and modeling should be minutely extendedwhich would enhance the results along with other relevant researches.
Keywords: start-up lost time; headway; cell-phone users; flow capacity.